Citizenship and integration - Gathmann, Christina; Garbers, Julio (Discussion paper series, 2022)
Several European countries have reformed their citizenship policies over the past decades. There is much to learn from their experience of how citizenship works; for whom it works; and what rules and policies matter for integration. The article surveys recent quasi-experimental evidence and field experiments from the social sciences on the link between eligibility rules, take-up and integration outcomes. Across countries and reforms, the evidence shows that faster access to citizenship increases take-up and improves the economic, educational, political and social integration of immigrants. Other eligibility rules like civic knowledge tests or application fees also impact who naturalizes and therefore benefits from citizenship. Birthright citizenship, which is much less common in Europe, turns out to be a powerful tool for getting second-generation immigrants off to a good start. Together, citizenship acts as a powerful catalyst benefiting immigrants as well as host countries.